Cost-effectiveness of long-acting versus short-acting contraception in adolescents: A systematic review - Yuni Fitriya; Arryan Rizqi Aulia Purnamasari; Fiki Amalia; Andari Wuri Astuti; Siti Roshaidai Binti Mohd Arifin Binti Mohd Arifin; Ajeng Viska Icanervilia (Journal of Health Technology Assessment in Midwifery, 2025)
Background: Child marriage remains a global reproductive health concern, placing adolescents at high risk of early pregnancy and obstetric complications. The selection of effective and cost-efficient contraceptive methods is essential to prevent unintended pregnancies. This study aimed to identify and compare scientific evidence on the cost-effectiveness of long-acting reversible contraception (LARC) versus short-acting reversible contraception (SARC) among married adolescents. Subjects and Method: This study was a systematic review guided by the PRISMA 2020 statement, employing the PICO framework. The population comprised married adolescents aged 10–19 years; the intervention included long-acting reversible contraceptives (IUDs and implants); the comparison involved short-acting reversible contraceptives (oral pills, injectables, and condoms); and the outcome focused on economic evaluation in health care. Literature searches were conducted in PubMed, ScienceDirect, and Google Scholar using MeSH-based keywords and Boolean operators. Articles meeting the inclusion criteria were screened using Rayyan, and their quality was assessed using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. Data were narratively synthesized based on parameters of cost-effectiveness, cost-utility, cost-benefit, Incremental Cost-Effectiveness Ratio (ICER), Average Cost-Effectiveness Ratio (ACER), and Quality-Adjusted Life Years (QALY). Results: Of the 471 articles identified, six met the inclusion criteria. Most studies employed Markov or decision tree models. The findings consistently indicated that LARC methods were more cost-saving compared to SARC. In Indonesia, IUDs had an ICER of USD 0.84 per pregnancy averted, compared to USD 3.76 for oral pills and USD 5.18 for injectables. In India, the etonogestrel implant achieved an Incremental Cost-Utility Ratio (ICUR) of USD 232 per QALY, well below the national willingness-to-pay threshold. In Kenya, the lowest cost per couple-year of protection was reported for IUDs at USD 4.87. Overall, LARC was shown to prevent more unintended pregnancies at a lower cost compared to SARC. Conclusion: Long-acting reversible contraceptives are more cost-effective than short-acting methods among married adolescents, supporting their prioritization in family planning policies to improve access and utilization.